Consistency of sex-based differences between treadmill and overground running using an inertial measurement unit (IMU) - Miqueleiz, U.; Aguado-Jimenez, R.; Lecumberri, P.; Gorostiaga, E. M. (Journal of Biomechanics, 2024)
Differences in running gait between treadmill and overground running has been subject of study, while consistency of group differences between running surfaces has not been previously analysed. This study examined both the differences between running surfaces and the consistency of sex-based differences between surfaces in some spatiotemporal and kinematic variables measured by an inertial measurement unit fastened over the lumbar spine. Thirty-two (sixteen females) endurance runners firstly performed overground and then treadmill (1 % inclination) runs at speeds between 9-21 km·h-1. Males showed lower flight time (FT) [moderate effect size (ES)] during treadmill running compared to overground, while females showed greater stride frequency (SF) (moderate ES), lower stride length (SL) (moderate ES), FT (moderate ES), and vertical (VT) trunk displacement (moderate ES), as well as greater medio-lateral (ML) trunk displacement (moderate ES). No differences in CT between surfaces were found (trivial to small). Furthermore, all the sex-differences were consistent between treadmill and overground running: Males showed lower SF (large and moderate ES, respectively), greater SL (large and moderate ES) and CT (moderate and large ES), lower FT (large ES), greater VT displacement (moderate to large ES), and lower ML displacement (moderate ES) than females. These results may be of interest to carefully transfer the running gait analyses between surfaces depending on sex.